Theta phase resetting and the error-related negativity. - Yeung, N; Bogacz, R; Holroyd, C; Nieuwenhuis, S; Cohen, J (2007)
It has been proposed that the error-related negativity (ERN) is generated by phase resetting of theta-band EEG oscillations. The present research evaluates a set of analysis methods that have recently been used to provide evidence for this hypothesis. To evaluate these methods, we apply each of them to two simulated data sets: one set that includes theta phase resetting and a second that comprises phasic peaks embedded in EEG noise. The results indicate that the analysis methods do not effectively distinguish between the two simulated data sets. In particular, the simulated data set constructed from phasic peaks, though containing no synchronization of ongoing EEG activity, demonstrates properties previously interpreted as supporting the synchronized oscillation account of the ERN. These findings suggest that the proposed analysis methods cannot provide unambiguous evidence that the ERN is generated by phase resetting of ongoing oscillations.